Estratégias de comunicação no atendimento em saúde a sujeitos surdos - Fortes, Luciana de Oliveira (2012)
Among human needs, communication is the most important. In health, it becomes even more relevant due to need of interaction between professional and patient, and due to the fact that inadequate communication, besides affecting treatement, can lead to unnecessary suffering for the patient and complicate the disease. Considering that the communication barrier hinders or prevents the interaction between deaf patients and health professionals, it can be overcome when they find strategies to communicate. The present study has aimed to investigate the perception of the hearing health care professional and deaf subjects in relation to the strategies used and to the aspects of communication established in health services. This quantitative, qualitative, descriptive and exploratory research was composed of 43 health professionals, who work in in a university hospital of a city in Rio Grande do Sul (RS), and 23 deaf people, who are students and teachers in a special school for deaf people and from federal institutions of higher education from two cities of RS. The instruments used were two questionnaires, both in written Portuguese language (PL), one to hearing health professionals, and another to deaf people. These had helped from the researcher, who is fluent in Sign Language (SL), from two SL interpreters who translated to LIBRAS (Brazilian Sign Language) each written question, in order to ensure those would understand the questions and to facilitate participants answers. Data collection was performed by the analysis of the 72 responses of the participants. The results have shown that the main strategy used by the deaf subject is writte PL, considered as a language that facilitates understanding. Mimics/gestures were evaluated by hearing professionals as a facilitator for understanding information during communication. The hearing companion is the strategy most used by both groups in health care. The deaf subject considers that speech (spoken language) used by professional hinders an understanding, while the health professional considers LIBRAS as the language that hinders the understanding of information in communication. Moreover, the deaf subjects believe the SL interpreter written PL are the strategies that contribute most to promote their autonomy and respect their privacy, respectively, while hearing professionals consider the use of hearing prosthesis. Therefore, we can see that there were differences of opinions among the deaf subjects and hearing professionals in relation to communication strategies. We can be concluded that this is one of the reasons that contribute to the maintenance of communication difficulties between hearing professionals and deaf subject in access to and health care.